2018
DOI: 10.14687/jhs.v15i3.5299
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the effects of swimming exercises and thera-band workouts on dynamic and static balance in children between 7-12 years of age<p>7-12 yaş arası çocuklarda yüzme egzersizi ve thera-band çalışmalarının dinamik ve statik dengeye etkisinin incelenmesi

Abstract: The aim of this study was to investigate the effects of swimming exercises and theraband workouts on dynamic and static balance in children aged 7-12 years. The study was conducted with 20 subjects aged 7-12 who were interested in swimming for at least 2 years and engaged in swimming training on a regular basis for 5 days per week. Informed consent was obtained from the parents and trainers of the participants about their voluntary participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Tan and Çolak [32], determined that core exercises increased balance levels in children aged 8-10 years. In another study, the effect of swimming and theraband exercises on balance was examined and it was concluded that balance development was significantly increased in the group performing the two exercises [33]. In this study, the effect of regular basketball training on balance was examined.…”
Section: Discussionmentioning
confidence: 93%
“…Tan and Çolak [32], determined that core exercises increased balance levels in children aged 8-10 years. In another study, the effect of swimming and theraband exercises on balance was examined and it was concluded that balance development was significantly increased in the group performing the two exercises [33]. In this study, the effect of regular basketball training on balance was examined.…”
Section: Discussionmentioning
confidence: 93%
“…Aggarwal et al (2010) reported that core stability and balance training had a positive effect on balance feature in their research on amateur male athletes. Kılınç et al (2018) reported that theraband studies played an important role in developing static and dynamic balance in their studies examining the effect of swimming exercise and theraband studies on dynamic and static balance in children between the ages of 7-12. Harput et al (2016) performed pliometric training along with volleyball training in 34 adolescent female volleyball players.…”
Section: Discussionmentioning
confidence: 99%
“…Böylece, yüzücülerin atletik performanslarını olumlu yönde etkileyeceği (p<0.05) (Sever ve Cicioğlu;2018:123), Thera-Bant kullanılarak kuvvet antrenmanı ve basketbol antrenmanı uygulayan deney grubu şut performansları ve tüm biyomotorik değerlerinde gelişim sağladıkları belirlenmiş (p<0.05) (Canlı, 2017:865), 13-16 yaş yüzücülere uyguladıkları kara ve direnç antrenmanların kuvvet değerlerine ve yüzme performansına etkisinin incelendiği araştırmada, yapılan antrenmanların özellikle direnç antrenmanlarının kara antrenmanlarına göre kuvvet ve yüzme derecelerinde daha etkili olduğu tespit edilmiştir (p<0.05) (Yapıcı, Maden & Fındıkoğlu, 2016:5278). 7-12 yaş çocuklarda yüzme egzersizi ve Thera-Band çalışmalarının sonuçları değerlendirildiğinde, Thera-Band egzersizlerinin statik ve dinamik denge gelişimine etkisinin olabileceği sonucuna varmışlardır (Kılınç, Günay, Kaplan & Bayrakdar, 2018:1448-1449. Bir başka araştırma sonucunda ise, 23 yaş yüzücülere uygulanan kara ve su içi direnç egzersizleri karşılaştırıldığında kas kuvvet gelişiminde aralarında fark olmadığı, hem su içi hem de su dışı direnç egzersizlerinin serbest yüzme antrenmanlarından daha çok kas kuvvetini geliştirebileceği sonucuna varmışlardır (Masso & Colado, 2010:68).…”
Section: Discussionunclassified